A low power broadband LC-VCO using high quality-factor multi-path stacked inductors in 14-nm FinFET. (April 2022) - Zheng, Libo; Li, Qiuliang; Xie, Haowei; Guo, Yufeng; Liu, Yi
Abstract: A broadband cross-coupled inductance-capacitance voltage-controlled oscillator (LC-VCO) is designed and implemented in 14-nm FinFET. To improve the tuning range and reduce phase noise of the VCO, novel multi-path stacked inductors are employed. A binary-weighted FinFET varactor array is utilized for band selection and frequency tuning at the same time without degrading the quality factor. The sizes of the FinFET devices are optimized to decrease the power consumption of the VCO. The chip size of the LC-VCO is 618 μm × 630 μm including testing pads. Measurement results demonstrate the frequency tuning range is 30.3%, phase noise is −112.5 dBc/Hz @ 1 MHz offset from 10.086 GHz carrier frequency and the power consumption is only 1.5 mW under 0.75 V supply voltage.